Severe and Fatal Multilobar Nonclassic Radiation Pneumonitis following Stereotactic Body Radiation Therapy (SBRT) for Treatment of Inoperable Non-Small-Cell Lung Cancer: A Report of Two Cases and Possible Enhancement by Concurrent Amiodarone - Anastasios Georgiou; Adam Farmer (Case Reports in Pulmonology)
Stereotactic body radiation therapy (SBRT) is considered the standard of care for treatment of inoperable early stage non-small cell carcinoma of the lung. SBRT delivers a very high dose of ionizing radiation to a relatively small region encompassing the tumor and spares a significant portion of the remaining lung from high doses. However, the conformal high dose comes at the expense of treating a larger volume of normal lung to lower doses. In general, this has been deemed to be acceptable with an overall lower risk of radiation pneumonitis. However, in the face of predisposing factors, the higher doses delivered by this technique may lead to an increase in radiation pneumonitis. We report on two patients being treated with SBRT in which severe radiation pneumonitis developed in spite of our radiation dosimetry being significantly below the acceptable limit for lung toxicity. Both patients developed a “fulminant” form of radiation pneumonitis with radiographic abnormalities well beyond the treated volume. In one patient, the disease proved fatal. Both patients were on amiodarone at the time SBRT was administered. Given the rarity of fulminant radiation pneumonitis, especially with the relatively small fields treated by SBRT, we suspect that amiodarone enhanced the pulmonary toxicity.